1999
DOI: 10.1080/03009749950155454
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of serum hepatic aminotransferases during treatment of rheumatoid arthritis with low-dose methotrexate: Risk factors and response to folic acid

Abstract: Sixty-six rheumatoid arthritis (RA) patients were analyzed retrospectively to assess the incidence and risk factors for elevation of serum hepatic aminotransferases during methotrexate (MTX) therapy. The effect of folate supplementation on serum ALT and RA activity was evaluated prospectively in 14 patients who showed a sustained high serum level of ALT. The frequency of elevation of serum AST or ALT was 4-5 times greater than in patients taking other DMARDs. Multivariate linear regression analysis demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Increased serum activities of these enzymes are extensively used as indicators of anti-inflammatory, therapy-induced hepatic lesion in rheumatic arthritis [40,41]. In the present study, elevated ALT and ALP activities were found in the serum of AIA control group when compared with the normal group.…”
Section: Resultssupporting
confidence: 59%
“…Increased serum activities of these enzymes are extensively used as indicators of anti-inflammatory, therapy-induced hepatic lesion in rheumatic arthritis [40,41]. In the present study, elevated ALT and ALP activities were found in the serum of AIA control group when compared with the normal group.…”
Section: Resultssupporting
confidence: 59%
“…As for RA patients, Kent et al identified obesity and hyperlipidemia as risk factors for the permanent discontinuation of MTX because of AST elevations [ 39 ]. Other studies showed that elevations of hepatic aminotransferases were more likely to occur in MTX users with obesity and hyperlipidemia [ 40 , 41 ]. In the present study, we identified obesity, type 2 diabetes, hyperlipidemia, and hyperuricemia as possible risk factors for persistent transaminitis during low-dose MTX treatment for RA.…”
Section: Discussionmentioning
confidence: 99%
“…4 ). Liver injury, represented by a transient or prolonged increase in AST and ALT levels is one of the adverse effects of MTX [ 21 ] and is reportedly observed in approximately 50% of patients who received it [ 22 ]. Because TCR is mainly eliminated from the body via metabolism by hepatic CYP3A, the increase in AST and ALT levels after MTX administration may explain the decreased clearance of TCR.…”
Section: Discussionmentioning
confidence: 99%